Interpretasi Makna Sistem Penamaan Orang Bugis: Kajian Semantik - Muhlis Muhlis; Hj. Ratnawati Umar; Hj. Andi Ebe; Irnawati Irnawati (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstrak: Interpretation of the Meaning of the Bugis Naming System: A Semantic Study. This study aims to describe the meaning of the names of the Bugis people. In this study, researchers collected several names and then processed and interpreted the meaning contained in the name. This research is qualitative research, the object of research is the Bugis community. The source of this research data is sourced from informants and the internet, data collection techniques using observation, interview, recording, and documentation techniques. Data analysis techniques use semantic interpretation techniques. The results showed that the Bugis people used to mostly give their children names in addition to being noble titles obtained from parents, as well as names derived from environmental events, forms of prayer, and children. Parents' expectations of their children.